Learning and memory in children with Noonan syndrome. Issue 9 (5th August 2013) - Pierpont, Elizabeth I.; Tworog‐Dube, Erica; Roberts, Amy E.
Abstract Genetic syndromes resulting from molecular alterations of the RAS–MAPK signaling cascade have become the focus of heightened interest among behavioral scientists due to discoveries that proteins within this pathway play an important role in memory formation and consolidation. Individuals with Noonan syndrome (NS), caused by germline mutations in the RAS–MAPK pathway, exhibit wide variability in cognitive and memory skills. The current study aimed to characterize memory deficits that occur in some affected individuals as a key step toward understanding the neurocognitive effects of dysregulated Ras signaling. Learning and memory skills were assessed among 29 children and adolescents with NS using the Wide Range Assessment of Memory and Learning, Second Edition. Performance across subdomains (verbal memory, visual memory and working memory) was compared, as well as the effect of response type (free recall vs. recognition). For immediate memory, children with NS performed significantly better on verbal memory tasks than on visual memory or working memory tasks. For delayed memory, verbal free recall tasks that depend heavily on prefrontal‐hippocampal networks were more challenging than recognition tasks that rely on more distributed temporal cortical regions. Additionally, verbal information presented in context was more easily retained than that presented in a rote format. The current study contributes to our knowledge of the effects of dysregulated RAS–MAPK signaling on the brain and behavior. Continued research on neurocognitive skills in NS has the potential to generate a novel conceptualization of how learning disabilities can arise from altered molecular processes within a specific biological pathway. © 2013 Wiley Periodicals, Inc.